Analysis of regulatory effect of miR-149-5p on Sphingosine-1-phosphate receptor 2 of pericytes and its neuroprotective molecular mechanism after acute cerebral ischemia reperfusion in rats. Issue 1 (1st January 2021) - Yan, Zhenxing; Deng, Yiting; Zou, Yang; Liu, Siqin; Li, Kaifeng; Yang, Juan; Guo, Xihua; He, Rongni; Zheng, Wenxia; Xie, Huifang
ABSTRACT: To investigate the effect of miR-149-5p on sphingosine-1-phosphate receptor 2 (S1PR2) expression level and contents of matrix metalloproteinase (MMP-9) and superoxide dismutase (SOD) in the pericytes after acute cerebral ischemia reperfusion in rats, so as to clarify the neuroprotective molecular mechanism induced by miR-149-5p and provide references for the treatment of neurological diseases, 60 male SD rats aged 7–8 weeks were selected and divided randomly into test group (establishing middle cerebral artery occlusion (MCAO) model) and control group (no modeling). Rat pericytes and peripheral cerebral infarction tissues were collected 12 h, 1 d, 3 d, 5 d, and 7 d after MCAO modeling, respectively. The pericytes were identified by immunofluorescence assay (IFA) and transfected with miR-149-5p. Fluorescence quantitative PCR (FQPCR) and Western blot were adopted to detect S1PR2 expression level. The expression of S1PR2 in MCAO model rats was detected by IFA. Immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) were used to detect the changes of MMP9 protein and mRNA levels of SOD1, SOD2, and SOD3 in brain tissue. The results showed that mRNA level and protein expression level of S1PR2 in the test group were higher than those in the control group three days after MCAO modeling ( P < 0.05); the expression of S1PR2 increased 12 h after MCAO modeling and returned to the normal level on the 5th day, and the content of MMP9 protein in brain tissue of the test group was significantly lower than that of the control group ( P < 0.05); the mRNA levels and SODs activity of SOD1, SOD2, and SOD3 in the test group were higher than those in the control group ( P < 0.05). Therefore, miR-149-5p played a neuroprotective role by regulating S1PR2 to change the expression levels of SODS and MMP9. Graphical Abstract: uf0001